Cashew By-Product as a Functional Substrate for the Development of Probiotic Fermented Milk - Herkenhoff, Marcos Edgar; de Medeiros, Igor Ucella Dantas; Garutti, Luiz Henrique Grotto; Salgaço, Mateus Kawata [UNESP]; Sivieri, Katia [UNESP]; Saad, Susana Marta Isay (MDPI, 2023)
Cashew (Anacardium occidentale) processing generates a by-product (CB) with potential for health benefits and that could be a favorable ingredient to be added to a probiotic food matrix. This study aimed to assess the functional attributes of CB in fermented milk with a probiotic and a starter culture using in vitro gastrointestinal conditions. Two formulations were tested, without CB (Control Formulation—CF) and with CB (Test Formulation—TF), and the two strains most adapted to CB, the probiotic Lacticaseibacillus paracasei subsp. paracasei F19® and the starter Streptococcus thermophilus ST-M6®, were chosen to be fermented in the CF and the TF. During a 28-day period of refrigeration (4 °C), both strains used in the CF and TF maintained a population above 8.0 log CFU/mL. Strains cultured in the TF had a significant increase in total phenolic compounds and greater antioxidant potential during their shelf life, along with improved survival of F19® after in vitro-simulated gastrointestinal conditions. Our study revealed the promising potential of CB in the probiotic beverage. The CB-containing formulation (TF) also exhibited higher phenolic content and antioxidant activity. Furthermore, it acted as a protector for bacteria during gastrointestinal simulation, highlighting its potential as a healthy and sustainable product.
Keywords: antioxidant activity; by-product; fermentability assay; in vitro digestion; prebiotic; probiotics